Genetic Resistance to Rhabdovirus Infection in Teleost Fish Is Paralleled to the Derived Cell Resistance Status - Verrier, Eloi R.; Langevin, Christelle; Tohry, Corinne; Houel, Armel; Ducrocq, Vincent; Benmansour, Abdenour; Quillet, Edwige; Boudinot, Pierre (PLOS ONE, 2012)
Genetic factors of resistance and predisposition to viral diseases explain a significant part of the clinical variability observed within host populations. Predisposition to viral diseases has been associated to MHC haplotypes and T cell immunity, but a growing repertoire of innate/intrinsic factors are implicated in the genetic determinism of the host susceptibility to viruses. In a long-term study of the genetics of host resistance to fish rhabdoviruses, we produced a collection of double-haploid rainbow trout clones showing a wide range of susceptibility to Viral Hemorrhagic Septicemia Virus (VHSV) waterborne infection. The susceptibility of fibroblastic cell lines derived from these clonal fish was fully consistent with the susceptibility of the parental fish clones. The mechanisms determining the host resistance therefore did not associate with specific host immunity, but rather with innate or intrinsic factors. One cell line was resistant to rhabdovirus infection due to the combination of an early interferon IFN induction - that was not observed in the susceptible cells - and of yet unknown factors that hamper the first steps of the viral cycle. The implication of IFN was well consistent with the wide range of resistance of this genetic background to VSHV and IHNV, to the birnavirus IPNV and the orthomyxovirus ISAV. Another cell line was even more refractory to the VHSV infection through different antiviral mechanisms. This collection of clonal fish and isogenic cell lines provides an interesting model to analyze the relative contribution of antiviral pathways to the resistance to different viruses.